Identification and Characterization of a Novel Aminoglycoside 3''-Nucleotidyltransferase, ANT(3'')-IId, From Acinetobacter lwoffii - Liang, Jialei; Zhou, Kexin; Li, Qiaoling; Dong, Xu; Zhang, Peiyao; Liu, Hongmao; Lin, Hailong; Zhang, Xueya; Lu, Junwan; Lin, Xi; Li, Kewei; Xu, Teng; et al. (Frontiers in Microbiology, 2021)
A novel plasmid-encoded aminoglycoside 3''-nucleotidyltransferase ANT(3'')-IId, was discovered in A. lwoffi strain H7 isolated from a chick on an animal farm in Wenzhou, China. The whole-genome of A. lwoffii H7 consisted of one chromosome and five plasmids (pH7-250, pH7-108, pH7-68, pH7-48 and pH7-11). ant(3'')-IId was identified as being encoded on pH7-250, sharing the highest amino acid identity of 50.64% with a function-known resistance gene, ant(3'')-IIb (KB849358.1). Susceptibility testing and enzyme kinetic parameter analysis were conducted to determine the function of the aminoglycoside 3''-nucleotidyltransferase. The ant(3'')-IId gene conferred resistance to spectinomycin and streptomycin (the MIC levels of both increased 16-fold compared with the control strain). Consistent with the MIC data, kinetic analysis revealed a narrow substrate profile including spectinomycin and streptomycin, with Kcat/Km ratios of 4.99 and 4.45×103 M-1 S-1, respectively. Sequencing analysis revealed that the ant(3'')-IId gene was associated with insertion sequences (IS) element (ΔISAba14-ΔISAba14-hp-orf-orf-orf1-ant(3'')-IId), and ant(3'')-IId were identified in plasmids from various Acinetobacter species. This study of the novel aminoglycoside 3''-nucleotidyltranferase ANT(3")-IId helps us further understand the functional and sequence characteristics of aminoglycoside 3''-nucleotidyltranferases, highlights the risk of resistance gene transfer among Acinetobacter species and suggests that attention should be given to the emergence of new aminoglycoside 3''-nucleotidyltranferase genes.